2016
DOI: 10.17795/ijcp-5007
|View full text |Cite
|
Sign up to set email alerts
|

HER-2/neu Overxpression in Esophageal Squamous Cell Carcinoma (ESCC) and Its Correlation with Patient’s Clinicopathological Features

Abstract: Background: HER-2/neu overexpression has been reported in various human cancers and identified as a significant predictor of poor survival. In this study HER-2/neu overexpression and its associations with clinicopathological characteristics were evaluated in patients with esophageal squamous cell carcinoma (ESCC). Methods: This cross-sectional study was performed on 64 patients with histological diagnosis of primary ESCC who underwent surgery for curative treatment. Immunohistochemistry (IHC) was used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Researchers have observed a significant correlation between CD10 expression and increasing grade 25 and lymph node involvement. 4 5 17 23 24 Complimenting this finding, a higher intensity of CD10 expression has been noted more often in grade III tumors, N2/N3 tumors compared to grade II tumors, and N0 / N1 tumors. Studies have reported that factors like necrosis, desmoplasia, and LVI are associated with aggressive nature, poor prognosis, and early recurrence/death.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Researchers have observed a significant correlation between CD10 expression and increasing grade 25 and lymph node involvement. 4 5 17 23 24 Complimenting this finding, a higher intensity of CD10 expression has been noted more often in grade III tumors, N2/N3 tumors compared to grade II tumors, and N0 / N1 tumors. Studies have reported that factors like necrosis, desmoplasia, and LVI are associated with aggressive nature, poor prognosis, and early recurrence/death.…”
Section: Discussionmentioning
confidence: 81%
“…Though majority of breast tumors are hormone dependent or express HER2 and have appropriate treatment targeting these pathways, triple-negative tumors form a significant number. Studies have reported a statistically significant correlation between CD10 expression and ER/PR negativity 2 3 4 5 7 and HER2/neu positivity, 2 3 but data correlating CD10 expression with molecular subtypes is limited. In the present study, CD10 expression was seen more often in triple negative and HER2 molecular subtypes of tumors compared to luminal A and luminal B subtypes and CD10 expression was of higher intensity in triple negative and HER2 types are the aggressive molecular variants, while in luminal A and Luminal B subtypes, expression was of lower intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meantime, they showed that HER2 expression was associated with moderately differentiated carcinoma cells without any significance. Raziee et al [16] studied 100 cases of gastric carcinoma in Iran and found a significant association of HER -2/Neu ( 26%) over expression with grade differentiation in Lauren's tumor. Further, in contrast with above mentioned, they had stated that their study did not reveal any association of HER2 expression with age, gender, location of tumor and depth of infiltration in patients.…”
Section: Discussionmentioning
confidence: 99%